An Open Letter to the Newer (And Senior) Members of TIMS - Howard, Ronald A. (Management Science, 1967)
It occurred to me that by writing a letter to the newer members I could assure them that there is not only an opportunity, but a real need for them to become involved with the operation of the Institute at both national and local levels.